Comparative Legal Analysis of Hoax Dissemination by Minors on Social Media: A Study of National Criminal Law and Islamic Criminal Law - Hermawan, Mhd Anggi; Ramadani (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2025)
Social media today functions not only as a communication tool but also as a platform for entertainment, education, and information dissemination. However, problems arise when false information (hoaxes) is spread—particularly when the perpetrators are minors. This study aims to analyse the differences in handling hoax dissemination by minors from the perspectives of criminal law and Islamic criminal law. Employing a normative juridical method with a comparative approach, the research draws on library-based data and case analysis. Four real-life cases of hoax dissemination via TikTok were examined, with identification of underage perpetrators based on user account content and behaviour. The findings reveal that, under national criminal law, the legal process prioritizes diversion as an initial step. If diversion fails, the case proceeds to court, where formal sanctions may be applied. In contrast, Islamic criminal law emphasizes returning the child to their parents, imposing ta’dībī (educational discipline) on the child, and ḍamān (compensatory liability) on the parents if the hoax involves defamation (qadhf). Key differences between the two systems include legal foundations, criminal responsibility, types of hoaxes, sanctions, and age thresholds. Nevertheless, both systems share a core principle: prioritizing rehabilitation and education over punitive measures. This study offers a novel comparative perspective and underscores the need for child-cantered legal frameworks in addressing the spread of hoaxes on social media.